Odpowiedzi

2009-12-02T14:33:03+01:00
1. 5x = 4-2y
4x + y =3

5x = 4 - 2y
y = - 4x + 3

5x = 4 - 2(4x + 3)
5x = 4 - 8x - 6
5x + 8x = -6 + 4
13x = 2/ 13
x = 2/13

tylko tyle bo teraz nie mam czasu;)

1 1 1
Najlepsza Odpowiedź!
2009-12-02T14:40:12+01:00
1. 5x = 4-2y
4x + y =3
5x+2y=4
4x+y=3 /(*-2)
5x+2y=4
-8x-2y=-6
-3x=-2
x=2/3

4*2/3+y=3
8/3 + y =3
y=3-8/3
y=-5/3


2.
6x - 3y = 9
x + 5y = - 9,5/(*-6)
6x - 3y = 9
-6x-30y=57
-33y=66/(-33)
y=-2

6x-3*(-2)=9
6x=-6+9/6
x=15/6
3 2 3
2009-12-02T14:47:59+01:00
1.
5x=4-2y
4x+y=3

5x=4-2y
y=3-4x

5x=4-2(3-4x)
y=3-4x

5x=4-6+8x
y=3-4x

5x=-2+8x
y=3-4x

5x-8x=-2
y=3-4x

-3x=-2 /:(-3)
y=3-4x

x=⅔
y=3-4*⅔

x=⅔
y=3-8/3

x=⅔
y=⅓


2.
2x-3y=9
x+5y=9,5

2x-3y=9
x=9,5-5y

2(9,5-5y)-3y=9
x=9,5-5y

19-10y-3y=9
x=9,5-5y

10y-3y=9-19
x=9,5-5y

7y=-10 /:7
x=9,5-5y

y=-10/7
x=9,5-5(-10/7)

y=-10/7
x=9,5+50/7

y=-10/7
x=... policz




7 4 7